2023
DOI: 10.1002/eap.2932
|View full text |Cite
|
Sign up to set email alerts
|

Forest restoration and fuels reduction work: Different pathways for achieving success in the Sierra Nevada

Scott L. Stephens,
Daniel E. Foster,
John J. Battles
et al.

Abstract: Fire suppression and past selective logging of large trees have fundamentally changed frequent‐fire adapted forests in California. The culmination of these changes produced forests that are vulnerable to catastrophic change by wildfire, drought, and bark beetles, with climate change exacerbating this vulnerability. Management options available to address this problem include mechanical treatments (Mech), prescribed fire (Fire), or combinations of these treatments (Mech + Fire). We quantify changes in forest st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…We also found that topographic-moisture conditions mediated the effects of fire as dry and intermediate sites exhibited larger shifts away from mesophication and toward sustaining future oak dominance. While mechanical treatments alone can be effective in limiting the primary management objective of reduced fire risk in dry western forests (see Hood et al, 2024;Stephens et al, 2023), we found that thinning without fire served to reinforce rather than limit the process of mesophication in eastern oak forests, shifting stands further away from the primary objective of sustaining oak dominance.…”
Section: Discussionmentioning
confidence: 76%
“…We also found that topographic-moisture conditions mediated the effects of fire as dry and intermediate sites exhibited larger shifts away from mesophication and toward sustaining future oak dominance. While mechanical treatments alone can be effective in limiting the primary management objective of reduced fire risk in dry western forests (see Hood et al, 2024;Stephens et al, 2023), we found that thinning without fire served to reinforce rather than limit the process of mesophication in eastern oak forests, shifting stands further away from the primary objective of sustaining oak dominance.…”
Section: Discussionmentioning
confidence: 76%
“…We used a custom decision matrix based on understory species cover, dominant tree species, fine fuel loads, and coarse woody fuel loads (Appendix 3). Similar to Stephens et al (2024), model selection breaks were determined based on each plot's Litter + FWD and CWD fuel loads relative to the median value (50% percentile) for the group. Plots with loads below the median value were assigned the fuel model with lower fuel loads, and those greater than the median were assigned the model with the greater fuel load.…”
Section: Fvs-ffe Modeled Prescribed Burnmentioning
confidence: 99%